Perencanaan strategis SDM dalam keunggulan kompetitif perbankan - Annisa, Maulidya (Maliki Interdisciplinary Journal, 2024)
In the competitive business world, all companies compete to be the most successful by designing careful strategies and involving all parts of the company. Successful companies are those that are able to create something new and unique, and are good at facing competition. A company must be careful in managing its environment, both internal and external. Although the relevant environment is very broad, including social forces as well as economic forces, the main aspect of a company’s environment is the industry in which the company competes. One of the internal environmental factors is the capability of its human resources. Therefore, every banking company must be able to facing competition from financial institutions by managing the environment proportionally. This research uses a literature study or literature review method which aims to plan human resource strategies for the competitive advantages faced by banks today.